2014
DOI: 10.1016/j.ejvs.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes in Chevalier Eversion Versus Conventional Carotid Endarterectomy

Abstract: C-CEA has the same rate of postoperative hypertension of standard-CEA, which is probably related to the sparing of baroreceptor apparatus, compared to standard E-CEA. The Chevalier procedure could represent an E-CEA technique with its inherent advantages, without penalties related to postoperative hypertension, commonly observed after E-CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
0
2
Order By: Relevance
“…[6,11,12] Several studies have demonstrated that hypertension caused by baroreflex dysfunction is associated with higher levels of cardiovascular and neurological mortality and morbidity. [1][2][3]13] Untreated hypertension is often considered to be one of the independent risk factors for poor outcome following CEA. While certain studies describe a positive relation between perioperative hypertension and the risk of poor neurological outcome or death after CEA, other studies have not found such a relationship.…”
Section: Discussionmentioning
confidence: 99%
“…[6,11,12] Several studies have demonstrated that hypertension caused by baroreflex dysfunction is associated with higher levels of cardiovascular and neurological mortality and morbidity. [1][2][3]13] Untreated hypertension is often considered to be one of the independent risk factors for poor outcome following CEA. While certain studies describe a positive relation between perioperative hypertension and the risk of poor neurological outcome or death after CEA, other studies have not found such a relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Клиника повреждения блуждающего нерва разнообразна: при повреждении возвратного гортанного нерва формируется парез голосовой связки, проявляющийся афонией и охриплостью голоса [8].…”
Section: Cite This Article Asunclassified
“…при повреждении же основного ствола могут наблюдаться вышеописанные симптомы, также дисфагия, синусовая тахикардия, гиперсаливация, свисание мягкого неба на стороне поражения, отсутствие небного и глоточного рефлекса, отклонение язычка в здоровую сторону [8].…”
Section: Cite This Article Asunclassified
“…The study by Marrocco-Trischitta et al does not specify whether techniques to preserve the sinus nerve, such as the technique described by Taurino et al, 6 were used during dissection of the carotid bulb. 6 Whether carotid sinus nerve function is preserved after e-CEA is a question of surgical finesse and is subject to diverse ongoing clinical trials.…”
Section: Replymentioning
confidence: 99%